PENGARUH EFISIENSI KEUANGAN DAN PEMBATASAN PEMBERIAN DANA PADA JUMLAH DONASI INDIVIDUAL - Abdurohman Muslim; Agus Purwanto (Diponegoro Journal of Accounting, 2013)
Individual donation takes an important role in a nonprofit organization’s life, includingZakat foundation. There are many factors that could influence individual donations. Based on Li, etall’s research, financial efficiency and solicitation type could influence how individual donorsspent their donation This study examines whether and how a nonprofit organization’s financialefficiency and its solicitation influence individual donations.Survey method was used to this study with 100 undergraduate students from DiponegoroUniversity, as a proxy of individual donor. The amount of individual donation given is shown indescriptive statistics. To examine the relationship between financial efficiency, solicitation type,and individual donation, Two-Ways Analysis of Variance (ANOVA) was applied.Align with the theory and previous studies, the result shows that financial efficiency andsolicitation type positively influence individual donation given by the donors.